ESTABLISHING A COMMUNICATIVE PRAGMATIC METHOD (Konferensiyalar | Conferences, 2024)
Currently, the process of formation of the communicative-pragmatic method is still observed, since some of the theories underlying it аre just emerging. The interest in this method is now since linguistics has realized the need to move from the study of minimal linguistic units to the study of speech activity and the consideration of language as a dynamic system, taking into account its functionality and anthropocentricity.